Performance of compliant liquid column damper for seismically excited structures - Bhattacharyya, Soumi; Ghosh, Aparna (Dey); Basu, Biswajit (Journal of Structural Engineering, 2024)
The Compliant Liquid Column Damper (CLCD) is a variation of the conventional Liquid Column Damper (LCD) that is applicable for the vibration control of relatively short period structures. Along with the long period structures short period structures are also highly vulnerable to the seismic excitation, as the frequency content of earthquake excitation is generally more broad-banded and richer in high frequency as compared to that of wind excitation. In the present study the equations of motion of the SDOF structural system with attached CLCD are formulated and a time domain parametric study with real earthquake input data is carried out. For a short period model structure the sensitivity of the design damper parameters are investigated and optimum values of the same are identified. Further, an experimental study on a base-excited stiff scaled structural model with CLCD is carried out for white noise and random loading. Identification of designed structural model followed by an experimental sensitivity study of the CLCD design parameters are presented. The optimal values of design parameters are identified and the performance of the optimally designed CLCD is examined for random base excitation. The efficacy of the CLCD for vibration mitigation of short period structures is thereby validated.